Binking Application: Early Detection of Computer Vision Syndrome - Nancy Jeane Tuturoong (East Asian Journal of Multidisciplinary Research, 2023)
Policies regarding the use of gadgets are very necessary at this time, especially during the COVID-19 pandemic, because at this time people inevitably have to be willing to learn and use technology such as gadgets / smartphones in order to meet their respective needs, studying, buying goods, reading news and other things, without a policy in the use of this technology will certainly have a negative impact on users such as Computer Vision Syndrome, this journal aims to determine the impact of Computer Vision Syndrome and also create an eye blink detection program which aims to prevent and detect eye blinks so as to avoid the negative effects of Computer Vision Syndrome such as eye disorders. This research was conducted using four students of the Faculty of Electrical Engineering, Sam Ratulangi University as sample’s data in making this Blink Detection program, the program was made through several references and several improvements until it was finally completed and the program could detect many eye blinks of gadget users and provide warnings to the user.